The effect of firm performance, managerial ownership, institutional ownership, audit committee size, and liquidity ratio on financial distress - Ofliyana Angga Dewi; Arum Ardianingsih; Dian Priatiningsih (Business, Accounting, and Knowledge Journal, 2024)
This study aims to determine the effect of company performance, managerial ownership, institutional ownership, audit committee size, and liquidity ratio on financial distress. This study took a sample of non-cyclical consumer companies listed on the Indonesia Stock Exchange (IDX) for the period 2017–2021. The research data was obtained from 50 companies. The data analysis methods used were descriptive analysis and multiple linear regression with a significance level of 0.05. The independent variables used were managerial ownership, institutional ownership, audit committee size, liquidity, and profitability. Another independent variable is company performance. The results of this study indicate that institutional ownership and liquidity ratio have an effect on financial distress, while company performance, managerial ownership, and committee size have no effect on financial distress.